1997
DOI: 10.2135/cropsci1997.0011183x003700010009x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Outcrossing Rate in Common Bean

Abstract: To assess genetic and environmental variation for outcrossing in common bean (Phaseolus vulgaris L.), a bulk of nine purplehypocotyled (dominant), black-seeded, common bean lines (pollen parents) and six green-hypocotyled (recessive), white-seeded, common bean lines (seed parents) representing Mexican germplasm were used to estimate outcrossing rate. The experiment was conducted at Irvine and Riverside, CA, in mid-May and mid-July of 1989 and 1991. Outcrossing estimates were based on the proportion of purplehy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 0 publications
3
49
0
2
Order By: Relevance
“…Moreover, recent studies have shown that low outcrossing rates do not prevent cultivated genes from moving in sympatric wild populations. These studies include both, autogamous and/or predominantly insect-pollinated species like soybean, bean or cotton (Ibarra Perez et al, 1997;Nakamaya and Yamaguchi, 2002;Van Deynze et al, 2005), as well as windpollinated autogamous species as rice or foxtail millet (Chen et al, 2004;Song et al, 2003;Wang et al, 1997;Zhang et al, 2003).…”
Section: D'andrea Et Almentioning
confidence: 99%
“…Moreover, recent studies have shown that low outcrossing rates do not prevent cultivated genes from moving in sympatric wild populations. These studies include both, autogamous and/or predominantly insect-pollinated species like soybean, bean or cotton (Ibarra Perez et al, 1997;Nakamaya and Yamaguchi, 2002;Van Deynze et al, 2005), as well as windpollinated autogamous species as rice or foxtail millet (Chen et al, 2004;Song et al, 2003;Wang et al, 1997;Zhang et al, 2003).…”
Section: D'andrea Et Almentioning
confidence: 99%
“…It is cultivated in many parts of world as dry beans and green beans (Ibarra-Perez et al 1997;Burle et al 2010). The sufficient amount of proteins (20-28%), carbohydrates, vitamins, dietary fiber (56%), micronutrients e.g., iron (Fe) (70 mg/ kg) and zinc (Zn) (33 mg/kg), vitamin B complex (niacin, riboflavin, folic acid and thiamine) and polyunsaturated fatty acids present in common bean have made it a potential staple food to overcome the problem of hunger (Pennington and Young 1990;Welch et al 2000;Broughton et al 2003;Guzman and Infante 2007).…”
Section: Introductionmentioning
confidence: 99%
“…There are about 50 species under the genus Phaseolus. Phaseolus vulgaris L. was follow-on from wild ancestors distributed from Northern Mexico to Northwestern Argentina (Ibarra-Perez et al, 1997;Debouck, 1999). The ancestors of P. vulgaris L. become visible to have created two distinctive gene pools one in Mesoamerica (Mexico and Central America) and the other in the Southern Andes, a mountain range in South America (Burle et al, 2010).…”
Section: Introductionmentioning
confidence: 99%